Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1002/jso.23777
|View full text |Cite
|
Sign up to set email alerts
|

Testis sparing surgery in the treatment of bilateral testicular germ cell tumors and solitary testicle tumors: A single institution experience

Abstract: TSS is acceptable from an oncological point of view, and it enables continuation of a patient's life without lifelong hormonal substitution. Additionally, local irradiation therapy could be delayed in patients with TIN who wish to father children, but with high local recurrence rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 26 publications
0
23
0
1
Order By: Relevance
“…This was shown in an analysis by Giannarini et al [10] reviewing the literature on testis-sparing procedures, which showed that 74.8% of resected tumors were of benign histology and would have been overtreated with radical orchiectomy. In the case of a germ cell tumor pathology, there is a high incidence of GCNIS (13.3-90.9%) [4,9,11,12,13]. GCNIS is associated with a significant risk of local recurrence.…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations
“…This was shown in an analysis by Giannarini et al [10] reviewing the literature on testis-sparing procedures, which showed that 74.8% of resected tumors were of benign histology and would have been overtreated with radical orchiectomy. In the case of a germ cell tumor pathology, there is a high incidence of GCNIS (13.3-90.9%) [4,9,11,12,13]. GCNIS is associated with a significant risk of local recurrence.…”
Section: Figmentioning
confidence: 99%
“…GCNIS is associated with a significant risk of local recurrence. Bojanovic et al [11] analyzed their collective with regard to local recurrence due to the presence of GCNIS. In patients without GCNIS, 10-year recurrence-free survival was 82%.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…Testosterone levels remained normal in all patients, though 2 became azoospermic after surgery. Paternity was achieved in 4 cases, 2 of which by spontaneous conception and 2 by assisted reproductive techniques [40]. The theoretical functional advantages of TSS must be tempered by the observation that postsurgical gonadal function in these patients may be inherently abnormal, related to preexisting germ cell dysfunction associated with testis cancer or represent damage secondary to ischemia from cord clamping, the creation of antisperm antibodies, and the effects of adjuvant radiation.…”
Section: Application To Adolescent Patients Extrapolating From the Amentioning
confidence: 99%
“…54 It is typically indicated for organ confined tumors less than 3 cm in clinical diameter with use of biopsies of the tumor bed to rule out adjacent ITGCN and assess margin status. 55 Adjuvant XRT can also reduce local recurrence rates, although this can affect long-term fertility.…”
Section: Bilateral Testicular Germ Cell Tumormentioning
confidence: 99%